CRITERIA FOR ASSESSING THE LEVEL OF PATRIOTISM OF CADETS AND LISTENERS OF HIGHER MILITARY EDUCATIONAL INSTITUTIONS - Muzaffarov Zikir Kahramanovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article covers the criteria for assessing the level of patriotism and shaping patriotism of cadets and listeners studying in higher military educational institutions.